Different degrees of expression of pulmonary fibrosis signs with intratracheal administration of bleomycin at different doses in male SD rats (a study aimed at helping to select the optimal bleomycin dose for modeling pulmonary fibrosis) - Tukhovskaya, Elena A.; Palikova, Yulia A.; Severyukhina, Maria S.; Ismailova, Alina M.; Palikov, Victor; Slashcheva, Gulsara A.; Borozdina, Natalya A.; Mikhaylov, Evgeniy S.; Kravchenko, Irina N.; Kazakov, Vitaly; Kazakova, Ekaterina N.; Kalabina, Elena A.; et al. (Frontiers in Pharmacology, 2025)
BackgroundPulmonary fibrosis (PF) is a life-threatening lung disease. PF develops under the influence of various damaging agents. To study new therapeutic strategies, a PF model with intratracheal administration of bleomycin (BLM) is used.MethodsWe studied the effect of different doses of BLM. The study was performed on male SD rats. BLM was administrated at doses of 0.5, 1.5, 2.5, 3, and 5 mg/kg. Animals were observed for 21 days for the following parameters: the overall health status, body weight gain, and external respiratory function. On the 22nd day, the lung weight, cellular composition of the bronchoalveolar fluid (BALF), and hydroxyproline content were determined, and the degree of lung fibrosis was histologically assessed.ResultsWith an increase in the BLM dose, the overall health status deteriorates, the function of external respiration worsens, BALF neutrophilic infiltration increases, and PF severity increases. The least marked PF manifestations were observed after the administration of BLM at a dose of 0.5 mg/kg, and the most marked manifestations were observed after the administration of BLM at a dose of 5 mg/kg.ConclusionResults obtained in the study demonstrate a dose-dependent effect of BLM on the PF severity, which provides information that will help select BLM dose suitable for obtaining desired degree of PF in animal models.